Rock Mechanics Laboratory Tests Relevant to the in-situ Stress Measurements at the 4850-level, Homestake Mine, Lead, South Dakota - Vigilante, Peter (My University, 2018)
Laboratory rock mechanics experiments were conducted on cores taken from the Sanford Underground Research Facility (SURF) (formerly of Homestake Mine) in Lead, South Dakota. Strength properties and their anisotropy were investigated in order to aid the interpretation of the hydraulic-fracturing stress measurements conducted in boreholes drilled down from the 4850’ level (1478 meters depth) of the mine. Brazilian disc tests, uniaxial and triaxial tests, and laboratory hydraulic fracturing tests were conducted on cores recovered from the kISMET (Permeability (k) and Induced Seismicity Management for Energy Technologies) project as well as those previously obtained as part of the Deep Underground Science and Engineering Laboratory (DUSEL) program. Brazilian disc tests revealed significantly higher tensile strength when samples were loaded normal to the foliation compared to when the samples were loaded parallel to the foliation, indicating clear tensile strength anisotropy. Uniaxial tests of the cores produced UCS results with an average value of 107.4 MPa for samples loaded parallel to foliation, and 88.1 MPa for samples loaded perpendicular to foliation. Triaxial dynamic moduli measurements conducted under confinement equivalent to in-situ stress magnitudes indicated a 18% increase in dynamic Young’s modulus between samples loaded parallel to foliation compared to perpendicular. Laboratory hydrofracture tests were conducted under various triaxial stress states to see whether potential shear failure along weak foliation planes, promoted by differential stress, could affect the apparent hydrofracture breakdown pressure. While the observed breakdown pressures did not indicate any clear influence of the rock anisotropy, some samples subject to differential stress showed lower breakdown pressure possibly caused by leak-off into fractures before peak pressure is reached.